Modification of Biodegradable Polyesters Using Electron Beam - M. Suhartini (PPIKSN-BATAN, 2013)
Poly(4-Hydroxybutirat)p4hb, Poly(butylene succinate-co-adipate) PBSA and Poly(e-caprolactone) PCL were electron beam (EB)-irradiated. Poly(4-Hydroxybutirat) was irradiated without any polyfunctional monomers (PFM). While PBSA and PCL were irradiated in the presence of polyfunctional monomers such asTrimethallyl isocyanurate (TMAIC), Polyethyleneglycol dimethacrylate (2G, 4G), Trimethylolpropane trimethacrylate (TMPT) and Tetramethylolmethane tetraacrylate (A-TMMT) at ambient temperature. Aim of the study is to improve the properties of biodegradable polyester. It was pointed out that crosslinking yield of P4HB (6.39% gel)was formed at dose of 90 kGy irradiated in vacuum conditions. Radiation degradation promoted, when P4HB was irradiated in air. The optimum crosslinking yield of PCL and PBSA respectively, were formed in the presence of 1% TMAIC at dose of 50 kGy. The biodegradability of the crosslinked PBSA evaluated by soil burial test is slightly retarded by increasing crosslinking yields.Received: 20 November 2013; Revised: 27 December 2013; Accepted: 31 December 2013